-1=-7y+3(y+7)

Simple and best practice solution for -1=-7y+3(y+7) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -1=-7y+3(y+7) equation:



-1=-7y+3(y+7)
We move all terms to the left:
-1-(-7y+3(y+7))=0
We calculate terms in parentheses: -(-7y+3(y+7)), so:
-7y+3(y+7)
We multiply parentheses
-7y+3y+21
We add all the numbers together, and all the variables
-4y+21
Back to the equation:
-(-4y+21)
We get rid of parentheses
4y-21-1=0
We add all the numbers together, and all the variables
4y-22=0
We move all terms containing y to the left, all other terms to the right
4y=22
y=22/4
y=5+1/2

See similar equations:

| 1/2x-4=3/4x+1 | | -7(v-7)=7v-49 | | -13=3+7x+5 | | 16x=186 | | 2x–15=5–3x | | −6n-20=−2n+4(1-3n) | | 6.10=(x-8)/2 | | w+6/4=4 | | 2/9x+3/8=7/12 | | 1-w=293 | | 3x+x+7=19 | | -7h=-4-9h | | 3x=10x-16 | | 14=-4k+9 | | 6d+2d-d-2=4d | | 8x+4(4x-3)=-(6x+4)-4 | | 1+6x=5x+1 | | 2n+6=n-3 | | 7x-4=20+10 | | p+7=8p+7 | | 8=2/3{9x-6} | | 3x=10-16 | | -14=4(w-6)-9w | | 4x5=5x | | F(x)=2(2)+2 | | –2g=–8−3g | | -4+6k-2k=k-4 | | 9v-4-4v=-5 | | 4x+9+6x=49 | | 3x​ −15=−7 | | 2(-2+1)-5x+2=-23 | | 26=30-3x |

Equations solver categories